ANSWER OF THE COWPEA THE SALINITY OF THE WATER OF IRRIGATION - Lima, Carlos José Gonçalves de Souza; Oliveira, Francisco de Assis de; Medeiros, José Francismar de; Oliveira, Mychelle Karla Teixeira; Almeida Júnior, Agenor Bezerra de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2007)
This work was accomplished with the objective of evaluating the effect of different levels of salinity of the irrigation water in the development of cowpea. The used design was it entirely randomized with five treatments (0.5, 2.13, 2.94, 3.5 and 5.0 dS m-1) and three replications. The plants were collected to the 45 days after sowing, being appraised: the diameter of the stem, number of nodules in the roots, height, number of leaves, leaf area, matter dries of the root, of the aerial part and matter total drought. The salinity influenced lineally in the vegetative growth of the cowpea, being all the characteristics analyzed reduced with the increase of the salinity. The most affected characteristics for the largest saline level were leaf area (65.90%), matter dries of the aerial part (66.94%) and matter dries of the roots (76.14%). The presence of nodules in the roots went affect drastically for the salinity, with a reduction of 98.71% in the largest level. The matter total drought accumulated by the caupi plants is distributed in 22.5% for the matter dries of the roots and 77.5% of the matter dries of the aerial part, of this, 61.2% and 38.8% are distributed for matter dries of the leaves and of the stem, respectively.